Thermal inactivation of compost suppressiveness implicates possible biological factors in disease management - Malandraki, Ioanna; Tjamos, Sotirios E.; Pantelides, Iakovos S; Paplomatas, Epaminondas J. (My University, 2008)
Verticillium wilt is a devastating disease of a wide range of herbaceous and woody plant hosts, incited by the soilborne fungus Verticillium dahliae. Since there are no chemical treatments to control the pathogen, management strategies are focused on preventive measures. In the present study, the microbial nature involved in the suppressiveness of a compost amendment (GR6, fabricated of horse manure, unbroken bedding hay + wood shavings and municipal green waste) against V. dahliae was investigated. For this purpose, eggplants grown in sterilised or non-sterilised compost were transplanted in soil infested with V. dahliae microsclerotia, amended or not with sterilised or non-sterilised compost. The most efficient treatments were those that included non-sterilised compost; therefore, the observed suppressiveness could be attributed to microbial agents. Several microbes were isolated from the root system of eggplants grown in the compost and tested in vitro against V. dahliae. Two bacterial strains identified as members of the Pseudomonas fluorescens complex and two fungal isolates belonging to Fusarium oxysporum were selected for further evaluation under glasshouse conditions. The ability of the microbial agents to reduce the percentage of diseased leaves compared to the control treatment was demonstrated. Moreover, it was shown that the most efficient bacterial strain was a rhizosphere and endophyte inhabitant. In a field experiment, the treatment where compost was applied both in the nursery and the field and treatments with F. oxysporum and P. fluorescens strains exhibited reduced disease severity; however, an increase in yield compared to the untreated control was not observed
Keywords: Phytopathogenic microorganisms--Biological control; Pseudomonas fluorescens; Verticillium dahliae; Bacteria; Equidae; Fungi; Fusarium oxysporum; Eggplant; Verticillium